Colloidal synthesis and properties of lanthanide orthophosphate nanophosphors - Klochkov, V.K.; Kavok, N.S.; Malyukin, Yu.V.; Masalov, A.A.; Vyagin, O.G. (Functional Materials, 2009)
Nanocrystals water solutions of activated lanthanides orthophosphates CePO₄:Tb³⁺, LaPO₄:Eu³⁺ have been obtained by colloidal synthesis. The solution solid phase possesses characteristic luminescent properties. Nanoparticles of about 2 nm size are stable in water and have a negative surface charge. The solution toxicity has been estimated.